o efeito da recuperação judicial no risco de falência: uma análise das empresas brasileiras listadas na B3 utilizando o modelo z”-score de Altman - Azzola, Afonso Henrique Barbosa (2024)
This dissertation aimed to analyze the phenomenon of judicial reorganization in the context of Brazilian companies, exploring its scientific contributions and practical effects on bankruptcy risk. The first study conducted a bibliometric analysis of academic production related to judicial reorganization, using the Scopus® and Spell® databases. The analysis identified a significant increase in publications during periods of economic crisis and legislative changes, such as the reform of Law 14.112/2020. However, it was observed that academic production has been predominantly reactive, with high author dispersion and a focus on legal and financial dimensions, leaving gaps in areas such as corporate governance and organizational culture. The study suggested the need for greater interdisciplinary cohesion and the development of a more proactive research agenda. The second study focused on the empirical analysis of the impact of judicial reorganization on the bankruptcy risk of Brazilian companies traded on B3, using the Altman Z"-Score as the main indicator. The sample included 22 companies that went through judicial reorganization processes, with a comparison of Z"-Scores in the year prior to the approval of the reorganization plan and in the year of its conclusion. By applying the Wilcoxon and Mann-Whitney U tests, the results indicated that judicial reorganization, for most of the companies analyzed, did not significantly reduce the bankruptcy risk. However, the Z" Score proved to be effective in predicting the survival of companies after the process, showing a clear distinction between companies that remained active and those that went bankrupt. The research concluded that, despite the relevance of the topic, there are significant gaps in the literature and limitations in the practical impact of judicial reorganization, especially regarding its ability to promote financial recovery. Future studies are suggested to explore new dimensions, such as the effectiveness of recovery practices in different sectors and regions, as well as extending the time horizon and fostering international collaboration for a broader understanding of the subject.